2021
DOI: 10.3390/en14144167
|View full text |Cite
|
Sign up to set email alerts
|

Energy Parameters of Miscanthus Biomass Pellets Supplemented with Copra Meal in Terms of Energy Consumption during the Pressure Agglomeration Process

Abstract: The process of pelleting miscanthus biomass often encounters issues related to the low durability of the obtained pellets and high energy inputs. To solve these issues, the use of copra meal as a supplement is proposed. This paper presents the results of research on energy parameters of miscanthus biomass pellets supplemented with copra meal in terms of energy consumption in the pressure agglomeration process. As part of this research, the energy parameters of miscanthus biomass, copra meal biomass, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…According to Szyszlak-Bargłowicz and co-authors [71], the process of pelleting miscanthus biomass often encounters problems related to the low durability of the pellets obtained and high energy expenditure. The solution to the problem is the use of an additive to crushed miscanthus, post-production residues from the production of coconut oil in the form of crushed coconut.…”
Section: Chou Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…According to Szyszlak-Bargłowicz and co-authors [71], the process of pelleting miscanthus biomass often encounters problems related to the low durability of the pellets obtained and high energy expenditure. The solution to the problem is the use of an additive to crushed miscanthus, post-production residues from the production of coconut oil in the form of crushed coconut.…”
Section: Chou Et Almentioning
confidence: 99%
“…The results obtained show that the energy consumption of the miscanthus biomass pelleting process can be significantly reduced by adding the remains of shredded coconut as a biocomponent. With the addition of coconut up to 30%, a granulate was obtained with a kinetic strength of over 95%, a density of over 1200 kg/m 3 and a bulk density of over 417 kg/m 3 , with a simultaneous reduction in energy expenditure for the granulation process by 44% [71].…”
Section: Chou Et Almentioning
confidence: 99%
“…Szufa et al [21] assessed the quality of pelleted miscanthus as solid fuel and as biocarbon-carrier for fertilizers. The quality of copra mealblended miscanthus pellets was also studied by Szyszlak-Bargłowicz et al [7] in relation to energy consumption of the pelleting process. The properties of pellets derived from different biomass materials including miscanthus and their combustion behaviour were also examined by Kasurinen et al [22] with focus on the toxicological effects caused by combusting the pellets in residential-scale boiler systems.…”
Section: Introductionmentioning
confidence: 99%
“…Miscanthus is generally characterized by a higher productivity rate when compared to other biomass materials such as wood; paradoxically, it is considered as a lower quality material due to its higher ash and relatively low lignin contents (Table 1) [5,6]. Although, both raw and pelleted biomass are suitable for energy production, studies have shown that the most bene cial way to energy production from biomass materials such as miscanthus is by subjecting the material to pressure agglomeration-related pelleting, and combustion afterwards (for energy production) [7][8][9]. There are several bene ts to the use of biomass pellets, including consistency in physico-chemical characteristics (which makes combustion much more stable and lowers the risk of slag formation); gravity feeding within thermal energy systems (due to homogeneous size and structure); ease of handling, storage and transportation over long distances (due to higher density); and increased economic output in relation to reduction in transportation and storage costs [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available solid fuel for combustion in domestic boilers is mainly sold in the form of pellets, which are produced chiefly from wood or waste containing wooden mass. Cereal straw and typical energy crops such as miscanthus are also used in large quantities for pellet production [ 5 , 6 ]. Any material amenable to pressure agglomeration, such as tobacco post-harvest waste, can also be used for this purpose [ 7 ].…”
Section: Introductionmentioning
confidence: 99%